KURIKULUM CINTA: MEMBANGUN PARADIGMA PENDIDIKAN BERBASIS KASIH SAYANG DI MADRASAH - Ifendi, Mahfud (As-Sulthan Journal of Education, 2025)
This article examines the "Love Curriculum" concept as a new paradigm in madrasah education initiated by the Ministry of Religion of the Republic of Indonesia in 2025. This research uses a qualitative approach with library research to analyze the concept of love curriculum. The results of the study show that the Love Curriculum is an educational approach that emphasizes the strengthening of human values ​​through love and affection to form the character of humane students, appreciate diversity, and uphold universal human values. This concept is a form of transformation of Islamic education that is responsive to the challenges of the times, at the same time affirming the role of the madrasa as a center for the formation of noble characters. While the basic values ​of the development of this love curriculum are nine, namely: Empathy, love, tolerance, justice and equality, respect and humility, humanity, cooperation and collaboration, justice and responsibility, and self-confidence and creativity. The implication is that the application of the values ​of love will shape the character of students who have noble and humane character. This curriculum not only revolutionized the learning approach in madrasahs but also strengthened the function of education as a vehicle for the formation of a whole and harmonious personality. With the integration of the values ​of love in the learning process, the madrasa is expected to be a safe, inclusive, and supportive environment for the emotional, social, and spiritual development of students, so that it has a positive impact on a more peaceful and civilized society and national life.